Field Emission Scanning Electron Microscopy (FESEM) characterisation of the porous silica nanoparticulate structure of marine diatoms - Gnanamoorthy, P.; Karthikeyan, V.; Prabu, V. Ashok (Journal of porous materials, 2014)
Diatoms are unicellular algae that synthesize cell wall with silica that has highly ornate features on the nano to microscale. The porous silica nanoparticulate structure of three marine centric and one pennate diatoms namely, Coscinodiscus concinnus, Coscinodiscus sp., Odontella mobiliensis and Navicula directa were investigated by Field Emission Scanning Electron Microscopy (FESEM). Important morphological features like porous pattern, topography, pore size and shape were studied. The external layer (cribellum) of C. concinnus was found to be consisting of a characteristic pentagonal array of pores which were star in shape and irregular in size, with a diameter of 224.7 nm and a pore-to-pore distance of 160.6 nm. The second diatom species investigated, Coscinodiscus sp. showed frustule with radially-oriented pattern of alternating grid-like arrangements of pores with honeycomb topography with pore diameter of 132.1 and distance between arrays were 61.01 nm. The O . mobiliensis images showed well organisation of holes (foramen) showed hexagonal organisation and all the pores are circular with same size and pores of 328.6 nm diameter with pore to pore distance was 252.8 nm. The girdle view of N. directa was about 5 μm in diameter with values showing striae are parallel in whole and porous were observed in N. directa in the range of 278.3 nm, the gaps between regularly arranged pores were 145.6 nm was clearly observed. The internal and external structures of all the diatom frustules were different in pore arrangements. The present study showed that high-resolution FESEM results revealed the silica nanostructure with nanoporous material exhibited interesting application in antireflection, drug delivery and heavy metal adsorbing studies, which should be investigated further research will be a subject of future proposals by a flat form of present investigation.